„Ich bin zu dick!“: verzerrte Gewichtseinschätzung bei Kindern und Jugendlichen in Deutschland - Röhrig, Silke; Giel, Katrin; Schneider, Sven (Monatsschrift Kinderheilkunde, 2012)
BackgroundOur study aimed at investigating to what extent the subjective assessment of weight deviates from the objectively measured body mass index (BMI).MethodsWith the help of bivariate analysis and logistic regression we analyzed the magnitude and pattern of a possible discrepancy between subjective and objective weight in male and female children and adolescents aged 11-17 in Germany in order to identify influencing factors. This investigation was based on the German Health Interview and Examination Survey for Children and Adolescents (KiGGS). Special attention was given to children and adolescents who overestimated their weight.ResultsFor 51% of the boys and girls examined in the age group 11-17 perception of their weight corresponded with their BMI. However, 47.7% of girls and 31.1% of boys overestimated their weight. Apart from gender other factors influencing weight perception included type of school, social status, and parents’ weight (p<05).ConclusionOur results show that a large number of the children and adolescents examined overestimate their weight. Behavioral preventive measures should take this into account.